SOCIAL ASSISTANCE IN BRAZIL. UNTAPPED POTENTIAL OF CITIZEN PARTICIPATION? - Cardoso Cekiera e Sousa, Chantal; Butowski, Krzysztof (The Copernicus Journal of Political Studies, 2018)
Brazil, the biggest country in South America creates the image of boundless land with unlimited richness of cultural diversity on a large scale. But its also creates big and very complicated social problems, which need to be solved. There is this huge number of citizens, who participate exclusively in poverty, hunger, misery, deprivation and violence. This article shows that the history of the assistance was complicated and not linear, often inhibited its development due to certain historical events as a military dictatorship, which really slowed development. The Brazilian social policy was perceived as very inefficient and ineffective in fighting poverty. The article aims to trace the historical and current social assistance programs in Brazil. There was practically no state-run social policy. Only in the era of industrialization workers’ rights were implemented because of the fear of revolution and strikes. Social rights, as provision of housing or facilities for education and health care services were only applied to the formally employed – mostly male – urban, industrial proletariat. The biggest group of agricultural labourers (the overwhelming majority of the wage-dependent population as well as the majority of women) and unclassified workers were excluded from these benefits. Help was received by the group that the regime considered as dangerous. Social resistance against the dictatorial rule was growing. It all started to change when the capital accumulation led to the creation of factories. In particular, the low human capital development was seen as a major cause of long-term poverty. New subjects like trade unions, active members of the middle class, the Catholic Church led to a public debate, the effect of which became a climate conducive to the adoption of the Constitution of 1988. Article 6 says that education, health, work, housing, leisure, security, social security, protection of motherhood and children, help for the poor and are social rights under the terms of this Constitution (Constitution of the Federative Republic of Brazil). This political agenda clearly pushed for the expansion and decentralization of public social spending. It has become a base for the social safety net. The solution for the problem became Conditional Cash Transfer (CCT) programs. Bolsa–Escola, Comunidade Solidária Program, Alfabetização Solidária Program and finally Bolsa Familia aim to reduce poverty by making welfare programs conditional upon the receivers’ actions. The assumption of purpose of these programs is to interrupt the inter-generational transmission of poverty. It can be also assumed that the aim of the Brazilian authorities was to achieve the effect of empowerment. The well-defined cashflows have resulted in the emergence of the phenomenon of empowerment, which has greatly raised the efficiency of social policy.